2003
DOI: 10.1007/s00431-003-1291-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid, nitrogen, water and energy content of a single stool sample in healthy children and children with cystic fibrosis

Abstract: Results from single stool samples yield clinically useful information concerning fat and energy. Single stool sample analysis is therefore useful for frequent monitoring of faecal fat and energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Therefore, the primary efficacy endpoint selected for the supplemental study relied on the spot fecal fat test from a single stool sample to assess steatorrhea. This is considered a valid method for assessing fecal fat content [30][31][32][33][34][35] and was selected based upon a review of the literature and input from the investigators and the CFF-TDN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the primary efficacy endpoint selected for the supplemental study relied on the spot fecal fat test from a single stool sample to assess steatorrhea. This is considered a valid method for assessing fecal fat content [30][31][32][33][34][35] and was selected based upon a review of the literature and input from the investigators and the CFF-TDN.…”
Section: Discussionmentioning
confidence: 99%
“…PEP: pancreatic enzyme product. fecal fat content was utilized to represent abnormal pancreatic function as determined per a review of the literature [30][31][32][33][34][35]. The baseline steatocrit taken during screening (representing treatment with the patient's previous pancreatic enzyme therapy) was compared to the dose stabilization and treatment measurements.…”
Section: Stool Collection and Analysismentioning
confidence: 99%
“…Although half of the respondents use stool microscopy with Sudan stain, it provides purely qualitative information and performs well only in the setting of marked fat malabsorption (>10% of daily fat intake) and a fat‐loaded diet 14 . The acid steatocrit is a simpler method of quantifying faecal fat, but still requires dietary fat loading and faecal collections 15–17 . Some data have suggested that the acid steatocrit in random faecal samples yields results of reasonable accuracy, 15,17 and might therefore be considered a semiquantitative alternative.…”
Section: Discussionmentioning
confidence: 99%
“…14 The acid steatocrit is a simpler method of quantifying faecal fat, but still requires dietary fat loading and faecal collections. [15][16][17] Some data have suggested that the acid steatocrit in random faecal samples yields results of reasonable accuracy, 15,17 and might therefore be considered a semiquantitative alternative. However, this test has not entered regular clinical practice and was not listed by any of the gastroenterologists in the present study as one they use for fat malabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Only seven small studies have reported on stool nutrient contents and intestinal nutrient absorption in healthy subjects. Two studies determined energy and nutrient stool contents of healthy children (Rivero-Marcotegui et al, 1998;Van den Neucker et al, 2003). Four studies focused on nutrient absorption in healthy adults, of which one study compared the nutrient absorption of European adolescents with that of elderly individuals (66-78 years) on diets with different energy densities in a metabolic unit setting (Southgate & Durnin, 1970).…”
Section: Discussionmentioning
confidence: 99%